Reposisi Pengaturan Netralitas Aparatur Sipil Negara Dalam Penyelenggaraan Pilkada - Permana, Bayu Indra; Septiandani, Dian; Sukarna, Kadi; Sukimin, Sukimin (JURNAL USM LAW REVIEW, 2022)
The purpose of this study is to analyze the neutrality regulation of State Civil Servant (ASN) neutrality in the current regional elections is in effect and how the ideal form of ASN neutrality regulation in the regional elections is viewed from the study of the regional elections Law and other derivative rules as well as the theory of legal objectives. Several regulations, ranging from laws and government law to joint decrees involving several ministries and institutions, were issued in order to limit the space for movement and ensure the neutrality of ASN is maintained in the implementation of regional elections. This research is expected to be able to find the ideal setting regarding ASN Neutrality in regional elections by analyzing several applicable regulations. This study uses a normative juridical approach by using secondary data through the study of legislation and literature searches. This research has a novel perspective, namely trying to find the ideal form of regulation of ASN neutrality in the regional elections in terms of several applicable laws and theories of legal objectives. The results of this study conclude that the neutrality of ASN in the regional elections is regulated by the ASN Law, Regional Elections Law, Government Law Discipline of Civil Servants, Government Law for the Development of Corps Spirit, and Code of Ethics for Civil Servants, Circular Letter of KASN, Circular Letter of Menpan-RB, and Joint Decrees of 5 Ministers/Heads of Institutions. In addition, it is necessary to reposition the ASN neutrality rules under one legal umbrella, namely the KASN Regulations. Tujuan penelitian ini untuk mengkaji pengaturan netralitas ASN dalam Pilkada yang berlaku saat ini dan bagaimana bentuk ideal pengaturan netralitas ASN dalam Pilkada ditinjau dari kajian pada UU Pilkada dan aturan turunan lainnya serta teori tujuan hukum. Beberapa regulasi mulai dari UU, PP, sampai dengan Keputusan Bersama yang melibatkan beberapa Kementerian/Lembaga diterbitkan dalam rangka membatasi ruang gerak dan menjamin netralitas ASN tetap terjaga dalam penyelenggaraan Pilkada. Penelitian ini diharapkan dapat menemukan pengaturan ideal terkait Netralitas ASN dalam Pilkada dengan menganalisa beberapa regulasi yang berlaku. Penelitian ini menggunakan pendekatan yuridis normatif dengan menggunakan data sekunder melalui studi perundang-undangan dan penelusuran literatur. Penelitian ini memiliki kebaruan perspektif yaitu berusaha menemukan bentuk ideal pengaturan netralitas ASN dalam Pilkada ditinjau dari beberapa perundang-undangan yang berlaku dan teori tujuan hukum. Hasil penelitian ini menyimpulkan bahwa, netralitas ASN dalam Pilkada diatur dalam UU ASN, UU Pilkada, PP Disiplin PNS, PP Pembinaan Jiwa Korps dan Kode Etik PNS , SE KASN, SE Menpan-RB, dan Keputusan Bersama 5 Menteri/Kepala Lembaga. Selain itu perlu mendudukan ulang aturan Netralitas ASN dalam satu payung hukum yaitu dalam Peraturan KASN.